The Contribution of Khmer Local Wisdom to Social Cohesion - Prak, Samphose; Leeka, Jaras; Baokham, Natthaphon (Journal of Graduate MCU KhonKaen Campus, 2025)
The objective of this paper, the Contribution of Khmer Local Wisdom to Social Cohesion is to foster Cambodian culture, which has been sustained for many generations from the past to the present day. Khmer local wisdom encompasses the traditional knowledge, practices, and cultural values that have been cultivated and preserved by Cambodian communities over generations. This article focuses on 1) to explores the role of Khmer local wisdom in fostering social cohesion, particularly in the context of Cambodia’s historical and contemporary challenges. 2) to apply the local wisdom, starting from community traditions, religious practices, and conflict resolution mechanisms, the study highlights in the real situation in the kingdom. 3) how to these cultural assets contribute to building trust, solidarity, and harmony within and across diverse groups. importantly, the findings reveal that Khmer local wisdom serves not only as a repository of cultural identity but also as a dynamic tool for addressing social fragmentation, promoting reconciliation, and enhancing communal resilience. Significantly, by investigating its practices in areas such as intergenerational relationships, community rituals, and local governance, the article underscores the enduring relevance of Khmer cultural heritage in strengthening societal bonds and fostering sustainable peace in Cambodia. Also, this academic paper has been done through the documentary sources such as Khmer books, report, journal articles, and other sources, related to physical evidence with real locals practicing of own local wisdom in the Kingdom of Cambodia so far.